Symbiotic nitrogen fixation response of Mucuna as affected by rhizobial inoculation in farmers fields in the derived savanna of Benin - Houngnandan, P.; Sanginga, P.; Woomer, P.L.; Vanlauwe, Bernard; Cleemput, O. van (2000)
Leguminous cover crops such as Mucuna pruriens (mucuna) have the potential to contribute to soil N and increase the yields of subsequent or associated cereal crops through symbiotic N fixation. It has often been assumed that mucuna will freely nodulate, fix N2 and therefore contribute to soil N. However, results of recent work have indicated mucuna's failure to nodulate in some farmers' fields in the derived savanna in Benin. One of the management practices that can help to improve mucuna establishment and growth is the use of rhizobial inocula to ensure compatibility between the symbiotic partners. Experiments were conducted in 1995 and 1996 on 15 farmers' fields located in three different villages (Eglimé, Zouzouvou and Tchi) in the derived savanna in Benin. The aim was to determine the response of mucuna to inoculation and examine the factors affecting it when grown in relay cropping with maize. The actual amount of N2 fixed by mucuna in the farmers' fields at 20 weeks after planting (WAP) averaged 60 kg N ha–1 (range: 41–76 kg N ha–1) representing 55% (range: 49–58%) of the plant total N. The result suggested that mucuna in these farmers' fields could not meet its total N demand for growth and seed production only by N2 fixation. It was estimated that after grain removal mucuna led to a net N contribution ranging from –37 to 30 kg N ha–1. Shoot dry weight at 20 WAP varied between 1.5 and 8.7 t ha–1 and N accumulation ranged from 22 to 193 kg N ha–1. Inoculation increased shoot dry matter by an average of 28% above the uninoculated treatments, but the increase depended on the field, location and year. For the combinations of inoculated treatments and farmers' fields, the response frequency was higher in Eglimé and Tchi than in Zouzouvou. The response to inoculated treatments was dependent on the field and inversely related to the numbers of rhizobia in the soil. Soil rhizobial populations ranged from 0 to >188 cells g–1 soil, and response to inoculation often occurred when numbers of indigenous rhizobia were <5 cells g–1 soil. In two farmers' fields at Zouzouvou where extractable P was below 10 μg g–1 soil, mucuna did not respond to rhizobial inoculation despite a higher population of rhizobia. Significant relationships between mycorrhizal colonization, growth and nodulation of mucuna were observed, and inoculated plants with rhizobia had a higher rate of colonization by arbuscular mycorrhizal fungi (%AMF) than uninoculated ones. Therefore, it was shown that mucuna will establish and fix N2 effectively in those fields where farmer's management practices such as good crop rotation and rhizobial inoculation allow a build up of AMF spores that might lead to a high degree of AMF infection and alleviate P deficiency.